PREPARING STUDENTS FOR THE TREATMENT OF A NEW TEACHER CONTENT, AN IMPORTANT PREREQUISITE FOR THE SUCCESSFUL IMPLEMENTATION OF THE TASK OF TEACHING - Zvezdan Arsić (International Journal of Cognitive Research in Science, Engineering and Education, 2013)
Success in any type of activity depends on thorough preparation. Processing of new teaching facilities, or the acquisition of new knowledge in the whole course of the educational process is one of the most important prerequisites for success in the implementation of the tasks of teaching. When it comes to this problem, the analysis of available peda-gogical - psychological and didactic and methodical literature, indicates that it mainly discuss the preparation of teachers, which is certainly needed. However, the implementation of teaching together and actively participating teachers and students, and the modern conception of school based on the students' activities. The above observations lead us to the conclusion that preparing students for teaching is equally important as the preparation of teachers, although it is somewhat more specific, given their status in the classroom.